2013
DOI: 10.1371/journal.pone.0068119
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Function and Evolution of the Eutherian-Specific Pluripotency Marker UTF1

Abstract: Embryogenesis in placental mammals is sustained by exquisite interplay between the embryo proper and placenta. UTF1 is a developmentally regulated gene expressed in both cell lineages. Here, we analyzed the consequence of loss of the UTF1 gene during mouse development. We found that homozygous UTF1 mutant newborn mice were significantly smaller than wild-type or heterozygous mutant mice, suggesting that placental insufficiency caused by the loss of UTF1 expression in extra-embryonic ectodermal cells at least i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 47 publications
(61 reference statements)
5
19
0
Order By: Relevance
“…The role of Sall4 in SSCs has been a challenge to decipher because of the early lethality of Sall4 -null mice [122]. In contrast, Utf1 -null mice have surprisingly mild defects, raising the possibility of redundancy with other transcription factors or context-specific effects [124]. Another candidate to have a role in SSCs is the transcription factor RHOX10, which is encoded by a member of a large X-linked homeobox gene cluster selectively expressed in the reproductive tract [125].…”
Section: Perspectivementioning
confidence: 99%
“…The role of Sall4 in SSCs has been a challenge to decipher because of the early lethality of Sall4 -null mice [122]. In contrast, Utf1 -null mice have surprisingly mild defects, raising the possibility of redundancy with other transcription factors or context-specific effects [124]. Another candidate to have a role in SSCs is the transcription factor RHOX10, which is encoded by a member of a large X-linked homeobox gene cluster selectively expressed in the reproductive tract [125].…”
Section: Perspectivementioning
confidence: 99%
“…A subsequent Utf1 ko ( Utf1 (−/−) ) mouse study, however, revealed that Utf1 is not critical for pluripotency, because viable and fertile Utf1 (−/−) mice can be obtained 14 . A noticeable Utf1 (−/−) phenotype reported in this study was developmental delay during embryogenesis that often caused smaller pups and neonatal death, which was attributed to reduced placental growth.…”
Section: Introductionmentioning
confidence: 99%
“…A noticeable Utf1 (−/−) phenotype reported in this study was developmental delay during embryogenesis that often caused smaller pups and neonatal death, which was attributed to reduced placental growth. However, the delay can be resolved during neonatal growth, thus resulting in phenotypically normal adult Utf1 (−/−) mice 14 . The in vivo relevance of Utf1-controlled maintenance of pluripotency, as proposed for ESCs in vitro , therefore remains an unresolved issue 13 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Notably, Esrrb null embryos survive until 10.5 days post coitum (dpc) and die due to placental abnormalities [73]. Similarly, while Dppa4, Dppa5 and Utf1 are specifically expressed in pluripotent cells in vivo and in culture, the impact of their absence is only observed during late embryonic stages, though redundancy among these genes has not yet been investigated [74][75][76].…”
Section: Regulatory Network For Pluripotency and Lineage Commitmentmentioning
confidence: 99%